Cognitive impact of early separation from migrant parents: A spectrum of risk and key mechanisms in child development contexts. A commentary on Hou et al., (2020). (December 2020) - Zhao, Chenyue; Egger, Helen
Abstract: Prolonged separation from migrant parents may lead to child development risks, despite the potential benefits from improved financial circumstances. Within the substantial literature on the health and well-being of the so-called left-behind children, the cognitive impact of parental migration has been inconclusive across different settings globally. In this issue, Hou et al.'s study in rural China focused on school-age children who experience persistent absence of both migrant parents since infancy, and revealed disadvantages in language comprehension outcomes among these children, despite the mitigating effect of higher household income. While results from this study are limited to the ongoing parent-child separation, previous absence of migrant parents has been suggested to have long-lasting negative effects in studies of adolescents in reunited families. Findings from Hou and colleagues' study highlight the needs to better understand migration-related parent-child separation during sensitive developmental periods in infancy and early childhood. A spectrum of risk due to parental migration should be established, accounting for the timing and duration of migration and care arrangements, in order to better identify the at-risk children in communities affected by out-migration. Future research should further explore the mediating and moderating factors in child's environments, and evaluate post-separation adjustment among reunited families after parents' return migration. Research evidence on these aspects will inform the development of tailored intervention programs for left-behind children, and strengthen the abilities of families and communities in best serving the needs of children affected by prolonged parental absence.